Оссолінеум у дзеркалі путівників Львовом (1871–1939) - Мовна, Маріанна (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
W artykule ukazano obraz Ossolineum widziany oczami autorów przewodników lwowskich, jego rolę w życiu kulturalnym Galicji od schyłku XIX w. do pierwszej połowy XX w. Najbogatsze pod względem objętości oraz najcenniejsze informacje historyczne zostały przedstawione w przewodnikach S. Kunasiewicza, M. Kowalczuka, F. Jaworskiego, J. Wiczkowskiego, B. Janusza, M. Orłowicza, A. Medyńskiego, które do dziś pozostają ważnym źródłem do dziejów Ossolineum. Na podstawie przewodników możemy prześledzić rozwój biblioteki i muzeum ZNiO w ciągu prawie 70 lat ich funkcjonowania. Autorzy opracowań wysoko oceniali Zakład im. Ossolińskich jako skarbnicę pamięci, a także ważny norodowy ośrodek nauki i kultury.

This article shows the image of the Ossolineum seen through the eyes of the authors of the Lviv guidebooks, its role in the cultural life of Galicia from the end of the 19th century to the first half of the 20th century. The largest in volume and the most valuable historical information was presented in the guidebooks by S. Kunasiewicz, M. Kowalczuk, F. Jaworski, J. Wiczkowski, B. Janusz, M. Orłowicz, A. Medyński, which until today remain an important source for the history of the Ossolineum. On the basis of the guidebooks we may follow the development of the Ossolineum library and museum during almost 70 years of its functioning. The authors of monographs highly valued the Ossolineum as the treasure chest of memory and also an important national centre of science and culture.
Ossolineum w świetle przewodników po Lwowie (1871–1939)
Keywords: Ossolineum; Muzeum xx. Lubomirskich; przewodniki; Lwów; the Ossolineum; Museum of the Lubomirski dukes; guidebooks; Lviv